PENGEMBANGAN MEDIA BOOKLET DALAM PEMBELAJARAN IKATAN KIMIA PADA MATA PELAJARAN KIMIA SEKOLAH MENENGAH ATAS - Irwan Irwan; ,Muhammad Asrori; Aloysius Mering (Universitas Tanjungpura, 2017)
AbstractThis research is aimed to produce media booklet design in chemical bonding study, to produce end product of booklet media in chemical bond study, to describe booklet media implementation on chemical bond material and to describe the result of chemical bond learning by using booklet media in SMA Negeri 1 Galing. This research is research development of booklet media with meggunakan development stage of Borg and Gall, with subject of research is class X student which amounted to 28 students. Stages of development of booklet media dilakkuan namely Research and information collecting, planing, Develop preliminary form of product, Preliminary field testing, Main product revision, Operational field testing and Final product revision. This research uses qualitative approach. From the results of questionnaires validation of media experts and validation of material experts, and student questionnaires about the media booklet, that the media booklet learning chemical bonding well used in learning chemical bonds. The results showed that the value of learning results obtained a value average of 77.14. High learning results show that learning booklets can be used in chemical bonding materials. Key words:Pengembangan, Hasil Belajar, Media Booklet, Ikatan Kimia.